2023
DOI: 10.1093/eurheartj/ehad274
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo syndrome is a coronary microvascular disease: experimental evidence

Abstract: Background and aims Takotsubo syndrome (TTS) is a conundrum without consensus about the cause. In a murine model of coronary microvascular dysfunction (CMD), abnormalities in myocardial perfusion played a key role in the development of TTS. Methods and results Vascular Kv1.5 channels connect coronary blood flow to myocardial metabolism and their deletion mimics the phenotype of CMD. To determine if TTS is related to CMD, wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 69 publications
0
15
0
2
Order By: Relevance
“…Indeed, the incidence of TTS during the COVID-19 pandemic increased likely due to the intense emotional stress caused by fear of getting seriously ill, fear for loved ones, changes to lifestyle habits including unemployment, economic crisis, and social distancing (8). On the other hand, in COVID-19 patients, irrespective of the severity of the clinical manifestation, several conditions which may favour TTS onset can occur: like catecholamine-induced myocyte injury and neurogenic myocardial stunning, cytokine storm, immune-mediated damage, direct viral myocyte injury, procoagulant state, microvascular coronary impairment due to endothelial injury, and vasospasm (9,10). The hypothesis is that SARS-COV-2 infection, even asymptomatic, may precipitate TTS onset in predisposed patients, where endothelial dysfunction plays a pivotal role as cause of microvascular impairment (11).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the incidence of TTS during the COVID-19 pandemic increased likely due to the intense emotional stress caused by fear of getting seriously ill, fear for loved ones, changes to lifestyle habits including unemployment, economic crisis, and social distancing (8). On the other hand, in COVID-19 patients, irrespective of the severity of the clinical manifestation, several conditions which may favour TTS onset can occur: like catecholamine-induced myocyte injury and neurogenic myocardial stunning, cytokine storm, immune-mediated damage, direct viral myocyte injury, procoagulant state, microvascular coronary impairment due to endothelial injury, and vasospasm (9,10). The hypothesis is that SARS-COV-2 infection, even asymptomatic, may precipitate TTS onset in predisposed patients, where endothelial dysfunction plays a pivotal role as cause of microvascular impairment (11).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Rivero et al assessing the index of microvascular resistance, showed the presence of acute microvascular damage with temporal evolution toward resolution that correlated with myocardial stunning recovery ( 25 ). Recently, in a mouse model of coronary microvascular dysfunction, a study demonstrated the significant role of disruptions in myocardial perfusion in the development of TTS ( 70 ). The impact of vascular Kv1.5 channels, which connect coronary blood flow to myocardial metabolism, in wild-type, Kv1.5 −/− , and TgKv1.5 −/− mice following transaortic constriction, was examined.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that transaortic constriction caused systolic apical ballooning and lower LV apex myocardial blood flow in Kv1.5 −/− mice, while other groups did not exhibit these effects. However, increasing myocardial blood flow through the use of chromonar, or inducing smooth muscle expression of Kv1.5 channels in TgKv1.5 −/− mice, restored perfusion and normalized ventricular function between the apex and base ( 70 ). These interesting findings highlight the contribution of flow regulation abnormalities between the LV apex and base on the pathophysiology of TTS and also emphasize the potential of restoring normal perfusion to recover ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…The IP administration of isoprenaline, which reproduces the RWMA as reported in patients, was first introduced by the Omerovic Lab (Gothenburg, Sweden) in 2013 in mice ( 16 ) and later in rats ( 14 ). The TS-like RWMA has also been reproduced in non-human primates ( 9 ) and rabbits ( 74 ). However, the most commonly used animal for TS research is the naïve rat (no pre-treatment or genetic modification), accounting for 72% of studies.…”
Section: Animal Models Of Takotsubo Syndromementioning
confidence: 99%